Effects of Ankle Pumping Exercises on Limb Edema in Critically ill Patients with Acute Respiratory Distress Syndrome - Gul, Humna; Fatima, Arooj; Ahmad, Ashfaq; Gilani, Syed Amir (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2021)
Acute Respiratory Distress Syndrome (ARDS) is an acute respiratory disease in which the respiratory activity of the lungs is compromised due to secretion of fluid in the alveoli of lungs and thus depriving the blood stream with optimal oxygen supply. Objective: To determine the effects of ankle pumping exercises on limb edema in critically ill patients with acute respiratory distress syndrome Methods: A sample of 67 patients was selected by using non-probability convenient sampling from different hospital settings. Ventilated patients or those having endotracheal tube, age between 40-65 years, and either gender were included in the study. Results: The effect of Range of Motion (ROM) on ARDS patients was as high as 91 %. There were 61(91.0) responders who experienced edema reduced by ankle pumping 54(80.6) found prone position and 13(19.4) found supine position effective 53(79.1) having resonant sound and 14(20.9) with hyper stony dullness 24(35.8) person having added sound and 43(64.2) crepitus sound in this study. In this study, 20 out of 67 patients who were admitted to the intensive care unit (ICU) developed acute onset of severe dyspnea, hypoxemia, and cyanosis and decreased respiratory system compliance, despite supplemental oxygen and mechanical ventilation. Edema had been reduced by ankle pumping in 61 subjects. Conclusions: Patients with ARDS report improvement in symptoms with physiotherapy treatment, ROM exercises had remarkable effects on such patients.